Building solutions with Microsoft Teams : understanding the Teams app developer platform - NS, Jenkins (Apress, 2021)
Explore Microsoft Teams and use its principal tools such as Node.js, npm, Yeoman, Gulp, TypeScript, and React to help you develop for Teams better. This book covers the core components and use cases for Teams apps and guides you through ideas for automation, provisioning, and implementation. Building Solutions with Microsoft Teams starts with an overview of the Microsoft Teams developer platform followed by how to set up your environment for building apps and solutions with Teams. You will then go through various features of conversational bots and learn how to create a bot. You will gain an understanding of the messaging extension and command actions along with tabs for personal, groups, and teams contexts. Moving forward, you will work with SharePoint and Teams together via SharePoint Framework. Finally, you will manage the Teams life cycle and see design guidelines supported by various case studies. After reading this book, you will be able to integrate solutions from Power Apps, Power Automate, Power BI, and Power Virtual agents by using accelerators. You will also be able to leverage your existing skills from SharePoint Framework development. You will: Extend the Teams developer platform capabilities Understand Microsoft Graph, including lifecycle management, collaboration, calling, and online meetings Create an app package for your Microsoft Teams app Connect web services to Microsoft Teams with webhooks.